Education And Eating Pattern As Risk Factors Of Diabetes Mellitus - Ninna Rohmawati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Education and eating pattern has significant contributions in determining incident of Diabetes Mellitus. Based on Riskesdas 2013, patient of Diabetes Mellitus who age >15 years increased from 5.7% (2007) to 6.9% (2013). Prevalence of Diabetes Mellitus in east java diagnosed by a doctor at 2.1%. The aim to determine risk factors affecting Diabetes Mellitus. This research was observational study. Subjects were patient of type 2 Diabetes Mellitus in RSD Kalisat who fulfilled inclusion criteria. Research subjects consisted of 40 people. Risk factors patients type 2 diabetes mellitus in the work area of Kalisat hospital Jember regency was in majority 45 years (82.5%), female (62.5%), basic education (77.5%), low levels of knowledge (47.5%), housewives 45%, eating pattern (87.5%), less sport activity (67.5%), less physical activity (55% ), overweight (37.5%) and not have the acts of hypertension (55%). Advice: education relation to knowledge needs to be improved, have good eating pattern, and need for regular physical activity.